Peter in the cloud of education - Joksimoski, Boban; Zdravkova, Katerina; Mihajlov, Dragan; CHorbev, Ivan (My University, 2014)
This paper presents the experience of a virtual student named Peter concerning various cloud computing services offered by the school where he is currently a freshman. The paper introduces and compares the differences between the traditional Plato’s classroom and today’s new classrooms powered by novel technologies. In the foreword, we present the milestones of cloud computing in education and research with particular attention focused on services currently available at the faculty as seen from Peter’s perspective. The paper also announces further system integration of several currently available services and the intention to extend cloud services from faculty to university level. Such ambitious shift should employ all the benefits, and at the same time overcome many challenges originating from the different aspects of cloud services. Therefore, it is crucial to standardise education in line with many everyday activities
Keywords: Cloud storage, e-Learning, Social networking, System integration